Vida conyugal y desigualdades de género en cali - Quintín Quilez, Pedro (Sociedad y Economía, 2008)
In the last decades, emphasis has been given to democratization of family life. According to some researchers, this behavior is related to higher feminine insertion in the labor market. In Cali (Colombia), however, wives, even with their own incomes, assume a higher share of domestic tasks and responsibilities. They also exhibit a lower participation in the allocation of family income, at least in the case here examined. Wife and husband, however, expressed similar levels of marital satisfaction.